A BIBLIOMETRIC ANALYSIS FOR AUDIT RESEARCH: EVIDENCE FROM ALGERIAN SCIENTIFIC JOURNALS PLATFORMS (ASJP) - Mohammed, Abbar; El-aid, Tahri; Houcine, Mahmoudi; Benziane, Roucham (International Journal of Accounting & Finance Review, 2022)
Addressing the increase of auditing in the current era, this study examines hotspots in auditing, research trends, and practical core works shaping this topic in Algeria since studies have yet to be conducted on the issue according to our specific orientation. By adopting a bibliometric analysis approach and searching with the keyword ’’audit’’ and its synonyms by different languages in the available cell allocated to the title within the database, Data(manuscripts) were automatically collected by author names, years of publication, titles, journals, abstracts and keywords up to 31st December 2021. The study input relies on 390 papers published in The Algerian Scientific Journals Platform (ASJP) from 2008 to 2021. The findings have shown a rapid increase in the number of publications, with a peak of 84 articles in 2021. The language commonly used was Arabic in (72 %) of the papers, and researchers performed their empirical contributions in sixteen countries, but the prevailing majority was in Algeria. Furthermore, The scientific landscape of auditing within accounting research is found to be fragmented into general classes: firstly, external audit (30%), secondly, internal audit (23%), while the scientific collaboration among authors was feeble and applied at (8.05%). However, the research with a specialized audit theme must be systematically adopted and developed in Algeria. JEL Classification Codes: M42, C55, C81.